The leadership investment : how the world's best organizations gain strategic advantage through leadership development - Fulmer, Robert M. (AMACOM, 2001)
"In The Leadership Investment, six of today's top organizations pull back the curtains to offer a revealing look into their own leadership development programs - programs that, dollar for dollar, repeatedly justify their costs. Based on an innovative, in-depth study of leadership development programs worldwide, this book offers concrete examples of how these organizations are using leadership development to consistently advance their strategic objectives."--Jacket